Aberrant Wnt/Beta-Catenin Pathway Activation in Dialysate-Induced Peritoneal Fibrosis - Guo, Yuanyuan; Sun, Lin; Xiao, Li; Gou, Rong; Fang, Yudong; Liang, Yan; Wang, Ruiqiang; Li, Ningjun; Liu, Fuyou; Tang, Lin (Frontiers in Pharmacology, 2017)
Peritoneal dialysis (PD)-associated peritoneal fibrosis is a chronic progress which induces ultrafiltration failure. It remains a challenge to prevent the progression of PD-associated fibrosis in clinic practice. Wnt/β-catenin pathway plays important role in many severe fibrotic diseases, here we investigated its contribution to the development of peritoneal damage. We isolated mesothelial cells (MC) from the effluent of PD patients and found that the expressions of Wnt1, Wnt5a, β-catenin and LEF1 were increased in patients with more than 1-year PD compared with patients who just started with PD (<1 month). The elevated expressions of Wnts and β-catenin were accompanied with changes in the expressions of E-cadherin，α-SMA, COL-I and FN mRNA and proteins, which are known related to mesothelial-mesenchymal transition (MMT). In addition, treatment with high glucose significantly increased the expression of Wnt1, Wnt5a, β-catenin and LEF1 as well as the expression of α-SMA, COL-I and FN in human peritoneal mesothelial cells (HPMC), whereas the expression of E-cadherin was reduced. Dickkopf-1 (DKK-1) is an endogenous inhibitor of Wnt/β-catenin signaling. Overexpression of DKK1 transgene significantly decreased the expression of β-catenin and attenuated the process of MMT as indicated by the decreased expression of α-SMA, COL-I and FN and the increased expression of E-cadherin. Furthermore, TGF-β1 treatment significantly activated the Wnt/β-catenin pathway in HPMCs, while DKK1 blocked the TGF-β1-induced Wnt signaling activation and significantly inhibited the process of MMT. These data suggest that the canonical Wnt/β-catenin pathway plays an important role in the MMT and fibrosis induced by PD.